Female sexual function in bladder cancer: A review of the evidence. Issue 1 (24th September 2022) - Martin, Rebecca; Renouf, Tessa; Rigby, Jeannie; Hafeez, Shaista; Thurairaja, Ramesh; Kumar, Pardeep; Cruickshank, Susanne; Van‐Hemelrijck, Mieke
Abstract: Background: Bladder cancer (BC) treatments are known to be invasive; nevertheless, research into the long‐term effects is limited and in the context of sexual function often male focussed. Female sexual dysfunction (FSD) has been reported in up to 75% of female patients. This systematic scoping review examines the literature on sexual consequences of BC in female patients. Objective: This study aimed to systematically evaluate the evidence on female sexual function in BC to identify areas of unmet need and research priorities. Evidence Acquisition: We performed a critical review of PubMed, PsychMed, CINAHL, MEDLINE and the Cochrane Library in March 2020 according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis (PRISMA) extension for Scoping Reviews statement following Levac et al. methodology. Identified reports were reviewed according to the Critical Appraisal Skills Programme (CASP) criteria. 45 publications were included. Evidence Synthesis: There was an inconsistent use of patient‐reported outcome measures (PROMs), with commonly used PROMs having a narrow symptom focus. However, common symptoms emerged: loss of desire, orgasmic disorders, vaginal dryness, dyspareunia, difficult intromission, reduced clitoral sensation, psychological concerns related to diagnosis, fear of contamination and body image. Sexual activity was reduced in most groups, despite women expressing a motivation to retain sexual function. The degree of symptom distress associated with FSD is underreported. Evidence emerged regarding a gap for women in clinician counselling and follow‐up. Conclusions: The patient's perspective of FSD in BC patients is poorly understood and under‐addressed in clinical practice. There have been very few qualitative studies of FSD in BC. Any intervention designed to address the problem must start with greater understanding of both the patients' and clinicians' perspective. Lay Summary: We examined the evidence on sexual consequences of BC in women. It is apparent that despite common themes of sexual dysfunction emerging, the problem is poorly understood and addressed in clinical practice.